Longitudinal vocabulary development in Australian urban Aboriginal children: Protective and risk factors. (3rd August 2017) - Short, K.; Eadie, P.; Descallar, J.; Comino, E.; Kemp, L.
Abstract: Background: Vocabulary is a key component of language that can impact on children's future literacy and communication. The gap between Australian Aboriginal and non‐Aboriginal children's reading and academic outcomes is well reported and similar to Indigenous/non‐Indigenous gaps in other nations. Determining factors that influence vocabulary acquisition over time and may be responsive to treatment is important for improving Aboriginal children's communication and academic outcomes. Aim: To determine what factors influence Australian urban Aboriginal children's receptive vocabulary acquisition and whether any of these are risks or protective for vocabulary development. Method: One hundred thirteen Aboriginal children in South Western Sydney from the longitudinal birth cohort Gudaga study were assessed on The Peabody Picture Vocabulary Test multiple times: 3 years, just prior to school entry, at the end of the first and second years of formal schooling. Multilevel models were used to determine the effects of 13 fixed and manipulable maternal, child, and family variables drawn from previous research. Results: Higher maternal education was found to be protective at 3 years and over time. The number of children in urban Australian Aboriginal households made an impact on vocabulary development and this varied over time. From 3 to 6 years, those with early poor non‐verbal cognitive skills had vocabulary skills that remained below those with stronger non‐verbal skills at 3 years. Girls exhibit an earlier advantage in vocabulary acquisition, but this difference is not sustained after 4 years of age. Conclusions: The risk and protective factors for vocabulary development in Australian Aboriginal children are similar to those identified in other studies with some variation related to the number of children in the home. In this limited set of predictors, maternal education, gender, non‐verbal cognitive skills, and the number of children in households were all shown to impact on the acquisition of vocabulary to 3 years and or the developmental trajectory over time.